1994
DOI: 10.1016/0014-5793(94)00840-x
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding sites for 3,3′‐diiodo‐l‐thyronine (3,3′‐T2) in rat liver mitochondria

Abstract: Specific binding sites for 3,3'-T2 can be detected in swollen and osmotically treated mitochondria (OTM) from normal and hypothyroid rat liver. In hypothyroid animals, maximal values of binding were obtained at 0°C and 20°C while values were lower at 37°C and no specific binding could be observed at 60°C. Binding was maximal at pH 6.4 and the mean values for the apparent association constant (Ka) and the binding capacity were on average 0.5 x 108 M -~ and 2.4 pmol/mg mitochondrial protein, respectively. No dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…cell metabolism. For example, 3,3′-T 2 binding sites were discovered in rat mitochondria, suggesting a role in metabolic regulation of the cell [25]. Also, stimulation of the cytochrome oxygenase was noted, but this data has not yet been independently confirmed.…”
Section: Discussionmentioning
confidence: 95%
“…cell metabolism. For example, 3,3′-T 2 binding sites were discovered in rat mitochondria, suggesting a role in metabolic regulation of the cell [25]. Also, stimulation of the cytochrome oxygenase was noted, but this data has not yet been independently confirmed.…”
Section: Discussionmentioning
confidence: 95%
“…Thyroid hormones, including T3, have been shown to stimulate metabolism, 58 to interact specifically with intact mitochondria, 54,59,60 and to alter C c O activity. 61,62 Retinoic acid, the degradative product of the essential vitamin A, has been tied to mitochondrial functions including transcriptional regulation, thermogenesis, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown (Goglia et al 1994 >) that T2s interact rapidly with the isolated COX complex. Such an inter¬ action leads to conformational changes and to the stimu¬ lation of enzymatic activity.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous paper, we reported that binding capacity was higher in euthyroid than in hypothyroid rats (Lanni et al 1994/)) indicating that the number of binding sites, like some components of the electron transport chain, is affected by T3. In the light of that finding, the lower binding capacity seen in hyperthyroid rats in the present study might seem to be a discrepancy, but it could be the consequence of a high endogenous occupancy of the binding sites in the hyperthyroid state.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation